2002
DOI: 10.1037/0033-2909.128.5.746
|View full text |Cite
|
Sign up to set email alerts
|

The association between psychopathology in fathers versus mothers and children's internalizing and externalizing behavior problems: A meta-analysis.

Abstract: In light of the selective focus on maternal (vs. paternal) psychopathology as a risk factor for child development, this meta-analysis examines the relative strength of the association between psychopathology in mothers versus fathers and the presence of internalizing and externalizing disorders in children. Associations were stronger between maternal than paternal psychopathology and the presence of internalizing (but not externalizing) problems in children, with all average effect sizes being small in magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

101
742
20
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 800 publications
(869 citation statements)
references
References 171 publications
101
742
20
6
Order By: Relevance
“…Although other studies reported that the role of fathers in upbringing is underestimated (Bögels & Phares, 2008;Liber et al, 2008) this was not confirmed in the present study. Cross-sectional research linking child and parent psychopathology found stronger associations of maternal than paternal psychopathology with internalizing problems in children (for a review see Connell & Goodman, 2002). In treatment studies, children's treatment outcome has been positively associated with paternal attendance and engagement in session (Podell & Kendall, 2011), and negatively associated with paternal rejection, and somatic, anxiety and depressive symptoms (Crawford & Manassis, 2001;Liber et al, 2008;Rapee, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies reported that the role of fathers in upbringing is underestimated (Bögels & Phares, 2008;Liber et al, 2008) this was not confirmed in the present study. Cross-sectional research linking child and parent psychopathology found stronger associations of maternal than paternal psychopathology with internalizing problems in children (for a review see Connell & Goodman, 2002). In treatment studies, children's treatment outcome has been positively associated with paternal attendance and engagement in session (Podell & Kendall, 2011), and negatively associated with paternal rejection, and somatic, anxiety and depressive symptoms (Crawford & Manassis, 2001;Liber et al, 2008;Rapee, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, parental psychopathology has been thought to impact the well-being of the child in many ways and by at least four different mechanisms including genetic transmission, the development of dysfunctional neuro-regulatory mechanisms from prenatal experiences, exposure to the parent's maladaptive affect, behavior and cognitions (including parenting) and finally, by contextual stressors associated with the psychiatric symptoms of one of the parents. 35 Furthermore, psychological problems in obese children may be explained by factors other than parental distress such as peer comments, or a low self-esteem. 1 Focusing on the influence of the characteristics of the fathers, no evidence for a mediator effect from paternal parenting behavior was found for the behavior problems of the children.…”
Section: Parent Characteristics and Psychopathology In Obesity V Decamentioning
confidence: 99%
“…We examine the impact of maternal and paternal depression separately. The role of maternal depression on offspring depression onset has received much more research attention than paternal depression (e.g., Phares, 1992) and a recent meta-analysis (Connell & Goodman, 2002) concluded that internalizing disorders, such as depression, in offspring were more closely related to depression in mothers than to depression in fathers. Paternal depression has not been found to increase the risk of offspring depression onset beyond maternal depression in most research (Brennan, Hammen, Katz, & Le Brocque, 2002;Lieb et al, 2002;Radke-Yarrow, Nottelmann, Martinez, Fox, & Belmont, 1992, although see Marchand & Hock, 1998).…”
Section: Impact Of Parent and Offspring Gendermentioning
confidence: 99%
“…Sheeber, Davis, and Hops (2002) proposed a model of same-gender transmission in which the family normalizes depressive behaviors in women and fails to reinforce instrumental behaviors in daughters. Modeling hypotheses also predict that there should be an interaction between the gender of the depressed parent and the gender of the child, with greater risk in same-gender pairs (Connell & Goodman, 2002). Unfortunately, few studies have explored this issue with respect to depression onset, and, to our knowledge, no research has examined the impact of parent and offspring gender on relations between parental depression and the course of offspring depression.…”
Section: Impact Of Parent and Offspring Gendermentioning
confidence: 99%